Respuesta :
Answer: 2 1/2 inches
Step-by-step explanation:
Michael puts 3 beads next to each other which are on a peice of string to make a bracelet. A bead has a width of 5/6 inch. Total width of the three beads will be the number of beads multiplied by the width of each bead. This will be:
= 3 × 5/6
= 15/6
= 2 1/2
The total width of the bead are 2 1/2 inches
Answer:
Expression: 3 x 5/6
fraction: 5/2
Step-by-step explanation:
Hi, to answer this question we simply have to multiply the number of beads (3) by the width of each bead (5/6 inch)
Mathematically speaking:
3 x 5/6 (this is the expression)
Solving the expression:
3 x 5/6= (3x5) / 6 = 15/6 = 5/2 inches (fraction)
Feel free to ask for more if needed or if you did not understand something.